1995
DOI: 10.1055/s-2007-1005784
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Resection of Large Colorectal Adenomas: A Combination of Snare and Laser Ablation

Abstract: The high clinical long-term success of our combined electro-laser resection is not only a result of complete endoscopic adenoma resection, but also of a strong control regimen. This technique is applicable to the treatment of large colorectal adenomas with curative intent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Moreover, complete retrieval of all specimens and histological determination of the depth of cancer invasion in EPMR are sometimes difficult [6][7][8][9][10][11][12][13]. It has been speculated that additional endoscopic treatment can achieve complete remission in most recurrent or residual tumors, but methods and safety in the treatment of these tumors have not been fully assessed.…”
mentioning
confidence: 99%
“…Moreover, complete retrieval of all specimens and histological determination of the depth of cancer invasion in EPMR are sometimes difficult [6][7][8][9][10][11][12][13]. It has been speculated that additional endoscopic treatment can achieve complete remission in most recurrent or residual tumors, but methods and safety in the treatment of these tumors have not been fully assessed.…”
mentioning
confidence: 99%
“…The efficacy of laser therapy for colorectal adenomas has also been evaluated by others [5,10,11,14,[16][17][18][19]. Mathus-Vliegen and Tytgat [20] investigated the effect of laser photoablation of colorectal adenomas in 196 adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…In the National Polyp Study [10], recur rence of adenomas was 32% after three years, and the only factor found to be associated with the detection of adeno mas with advanced pathological features was the number of adenomas at study entry. In a prospective study of large adenomas, mainly with a villous histology [68], a recur rence after polypectomy occurred in 28 % after a mean fol low-up of 1.4 years. In several follow-up studies of patients with colorectal adenomas, the recurrence rate for adeno mas was relatively low (6-33%) [23,40,69], but up to 59% after three years in a smaller study [70].…”
Section: Recurrence Ratesmentioning
confidence: 99%